When to buy; and when to sell a bushel of corn - Potter, George Percival (My University, 1907)
Introduction: One of the greatest problems confronting the American people of to-day is the food supply. In the United States we consume something like 14,000,000 tons of grain as human food and about 6,000,000 tons of beef annually. The amount of beef consumed annually by each person in the U. S. amounts to about 150 pounds. Every pound of beef produced by a choice feeder is worth from one to three cents more than that of the scrub. As to the time of year to feed, men differ. Many of our largest cattle feeders claim they cannot afford to feed during the winter months, as it requires more feed per pound of gain. The question of shelter and yards is very important. At the Experiment Station of Kansas there was a saving of 12 per cent in cost of feed, on steers well cared for, as compared with those that had but poor shelter and care. An experiment, the average of which out of 100 hogs in winter and 99 in summer, shoes a saving of 11 per cent in favor of summer feeding. Corn will perhaps even hold its place as the chief feed for fattening stock and especially cattle and hogs. It is safe to feed for either grass or dry-lot feeding. In the feeding experiments of the Kansas Station they have been unable to find any combination of feeds that will equal corn and cob meal and good alfalfa hay. It takes all the way from 400 to 1500 pounds of feed to produce a hundred pounds of gain, the amount depending on the kinds of feed used and the length of the feeding period. From a fat-stock show record, the cost of gain is given as $4.03 for calves, $7.98 for yearlings, and $12.54 for two-year-olds. The amount of grain required…
Citation: Potter, George Percival. When to buy; and when to sell a bushel of corn. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Purchasing Corn; Selling Corn; Agriculture Market; Agricultural Economics; Theses